PENGARUH PENERAPAN PENALARAN BERBASIS KONSEP MELALUI STRATEGI PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) TERHADAP PRESTASI BELAJAR SISWA PADA MATERI REDOKS - Sari, Betania Ratna; Suhartono, Suhartono; Darwis, Darsef (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to determine the effect of concept-based reasoning through learning strategy Process Oriented Guided Inquiry Learning (POGIL) to student achievement on the redox subject. This type of research is a quasi-experimental research with a Non-equivalent Control Group Design. The sampling used purposive sampling technique, which obtained by two classes, one as control class using Guided Inquiry Learning (GIL) and the other as experiment class using Process Oriented Guided Inquiry Learning (POGIL). Generated data during the study was analyzed by using descriptive and inferential statistical analysis of t-test. The average posttest grade of the control class is 66.91 while in the experimental class is 71.30. The results showed that there was a difference of chemistry learning achievement in control class and experiment class with tcount = 3.0810; ttable = 1.668 (tcount> ttable). The existence of these differences indicates that the application of concept-based reasoning through Process Oriented Guided Inquiry Learning (POGIL) strategy has a positive effect to students learning achievement on the redox subject. Keywords: POGIL Learning, Learning Achievement, Redox